2010
DOI: 10.1093/brain/awp337
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting poly(ADP-ribose) polymerase: a potential therapy against oligodendrocyte death

Abstract: Oligodendrocyte loss and demyelination are major pathological hallmarks of multiple sclerosis. In pattern III lesions, inflammation is minor in the early stages, and oligodendrocyte apoptosis prevails, which appears to be mediated at least in part through mitochondrial injury. Here, we demonstrate poly(ADP-ribose) polymerase activation and apoptosis inducing factor nuclear translocation within apoptotic oligodendrocytes in such multiple sclerosis lesions. The same morphological and molecular pathology was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
113
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 51 publications
10
113
1
Order By: Relevance
“…These observations suggest that PARP-1 activation occurs downstream of ERK1/2 activation and that the ERK/PARP pathway is involved in catalpol-mediated cytoprotection. PARP-1 activation is associated with the degeneration of OL processes and mediates OL loss and demyelination in experimental models of multiple sclerosis 48, 49. These morphological degeneration were also observed in PreOLs in our ischemic model, as shown by reduced process complexity and decreased myelination, further confirming the role of PARP-1 activation in PreOL injury.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These observations suggest that PARP-1 activation occurs downstream of ERK1/2 activation and that the ERK/PARP pathway is involved in catalpol-mediated cytoprotection. PARP-1 activation is associated with the degeneration of OL processes and mediates OL loss and demyelination in experimental models of multiple sclerosis 48, 49. These morphological degeneration were also observed in PreOLs in our ischemic model, as shown by reduced process complexity and decreased myelination, further confirming the role of PARP-1 activation in PreOL injury.…”
Section: Discussionsupporting
confidence: 84%
“…PARP-1 has been implicated in caspase-independent cell death due to its role in cellular NAD depletion, which further induces energy failure, mitochondrial depolarization, MPT pore opening, and apoptosis-inducing factor translocation in response to stress 46, 47. A recent study indicated that PARP-1 plays important roles in OL death 48. In an in vitro model of ischemia, ERK1/2-mediated PARP-1 activation was involved in OL death in a caspase-independent manner 20.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, massive alterations in respiratory chain proteins and mitochondrial DNA were reported in a case of acute MS lesions (Mahad et al, 2008). Observation of MS preactive lesions ex vivo or in a model of demyelination induced by cuprizone indicated that apoptosis in oligodendrocytes occurred through the mitochondrial pathway by means of PARP activation and caspase-independent translocation of the apoptosis inducing factor (AIF) from mitochondria to nucleus (Veto et al, 2010). Inhibition of poly(ADP-ribose) polymerase-impaired oligodendrocyte depletion further supported a role of PARP in the pathogenesis of MS lesions.…”
Section: Inflammation and Apoptosis At Central Nervous System Level Imentioning
confidence: 99%
“…Mitochondrial injury, which is most likely induced by reactive oxygen and nitrogen species [27,28], has been suggested as one possible mechanism of neurodegeneration in AD, Parkinson's disease, and MS [29]. Free radicals are produced through different pathways, including oxidative burst in activated microglia [30], and liberation of toxic iron from intracellular stores [31] as well as from mitochondrial injury themselves [32]. In MS, this pathway of tissue injury apparently is dominantly driven by the inflammatory process; however, amyloid toxicity may induce oxidative damage directly through mitochondrial injury as well as indirectly through microglia activation in AD.…”
Section: Current Research Investigating the Effects Of Aqp4 On Neuroimentioning
confidence: 99%